Metal–Organic Framework‐Derived Copper Nanoparticle@Carbon Nanocomposites as Peroxidase Mimics for Colorimetric Sensing of Ascorbic Acid. Issue 49 (21st October 2014) - Tan, Hongliang; Ma, Chanjiao; Gao, Li; Li, Qian; Song, Yonghai; Xu, Fugang; Wang, Tao; Wang, Li
Abstract Metal–organic frameworks (MOFs) have emerged as very fascinating functional materials due to their diversity nature. A nanocomposite consisting of copper nanoparticles dispersed within a carbon matrix (Cu NPs@C) is prepared through a one‐pot thermolysis of copper‐based metal–organic framework precursors. Cu NPs@C can catalyze the oxidation of 3, 3′, 5, 5′‐tetramethylbenzidine (TMB) to form a colored product in the presence of H2O2. As a peroxidase mimic, Cu NPs@C not only has the advantages of low cost, high stability, and easy preparation, but also follows Michaelis–Menten behaviors and shows strong affinity to H2O2. As the Cu NPs' surfaces are free from stabilizing agent, Cu NPs@C exhibited a higher affinity to H2O2 than horseradish peroxidase. On the basis of the inhibitory effect of ascorbic acid (AA) on oxidation of TMB, this system serves as a colorimetric method for the detection of AA, suggesting that the present work would expand the potential applications of MOF‐derived nanocomposites in biomedical fields.